Validating and profiling lifelong learning attributes among academic staff in Malaysian islamic tertiary institutions - Aldaba, Abdulmajid Mohammed Abdulwahab; Saad, Mohammad Azannee; Zubairi, Ainol Madziah (IIUM Press, 2026)
This study validates and profiles lifelong learning attributes (LLLA) among academic staff in Malaysian Islamic tertiary institutions. To addressthe absence of context-sensitive measures that integrate Islamic epistemological principles with contemporary lifelong learning theory, a cross-sectional survey was administered to 294 academic staff from two Islamic universities using a five-point Likert-scale instrument. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to examine the psychometric structure of the LLLA construct. The analyses supported a reliable five-factor, 20-item model encompassing goal setting, application of knowledge and skills, self-direction and evaluation, locating information, and adaptable learning strategies. The model demonstrated satisfactory fit indices, strong internal consistency, and clear evidence of convergent and discriminant validity. Descriptive findings indicated generally high levels of LLLA, with the exception of locating information, which showed comparatively lower scores. The study contributes novel insights by developing and validating an Islamically informed measurement modelfor lifelong learning in higher education, thereby extending Knapper and Cropley’s framework into an Islamic tertiary context. The validated instrument provides a robust tool for assessing LLLA and offers actionable evidence to support academic staff development and institutional planning within Islamic higher education.